The economic burden of stent thrombosis: a review of the literature. (14th October 2021) - Duff, S; Mafilios, M S; Stewart, A B; Hasegawa, J T
Abstract: Introduction: Stent thrombosis (ST) is a rare yet potentially serious complication associated with percutaneous coronary intervention (PCI). The high morbidity and mortality related to ST is well-documented, but the economic burden is less clear. Patients experiencing ST after PCI may have higher utilization of medical resources compared to patients without ST including longer inpatient stays, rehospitalizations, additional procedures, and increased pharmacotherapy use. Purpose: This targeted literature review explores the medical resource use and costs to manage ST in patients treated with PCI. Methods: We conducted a PubMed search of literature published from 2000–2020. In addition to publication year, inclusion criteria were: focus on economic burden, cost, or ST management; coronary disease patients; and English language. Two researchers selected and reviewed eligible studies as well as reference lists of included papers. Results: From a total of 891 citations identified, 9 studies reported medical resource use and costs of ST. Because ST typically presents as severe ischemia or myocardial infarction (MI), treatment is emergent and usually consists of admission for balloon angioplasty or PCI with stent. Studies in the United States (US), Italy, and Japan documented varying likelihoods of these interventions – differentiated by ST timing (i.e., early, late, or very late) and initial PCI type – which impacts the cost of ST management. The per-patient episodic cost of ST management was quantified in US and European studies. The range in US dollars (USD) was $3, 600-$36, 180 which varied by ST timing and types of resources included. In one US study that reported detailed cost categories, the catheterization lab was responsible for nearly half of the total ST management cost. Estimates for France and Spain ranged from €926–€3, 737; the primary factor that influenced these costs was the patient discharge status (alive or dead). The national economic burden of ST was quantified in two US studies. The annual estimated costs of ST to the US healthcare system were $40 million (2011 USD; very late ST only) and $65 million (2000 USD). Inflating these estimates to 2020 USD results in an annual economic burden of $52 million–$123 million. None of the identified studies comprehensively documented non-medical direct costs or indirect costs of ST in their results. Conclusions: Few robust, comprehensive, and contemporary studies of the economic burden of ST have been published. ST costs are driven by management of nonfatal MI and repeat PCI and likely vary by ST timing. However, the magnitude of non-medical costs is uncertain and, therefore, published data underestimate total ST economic burden. The findings from this review are particularly insightful since future prospective studies focused on the economic impact of ST may be unlikely. Stakeholders may find the clinical benefits of ST reduction more compelling than the economic impact. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott Vascular